Reproductive Biology of Striped Snakehead (Channa striata, Bloch, 1793) in Floodplain of Lubuk Lampam, South Sumatra (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Striped Snakehead (Channa striata) is one of the fish species inhabiting the flooded floodplain. Currently, the striped snakehead fish population in the Lubuk Lampam floodplain is undergoing a significant decline due to continuous and unregulated fishing activities. To prevent this population decline, there is a need for comprehensive efforts in managing their reproduction. The objective of this study was to investigate the reproductive behavior of striped snakehead fish in the floodplain of Lubuk Lampam, South Sumatra. The research spanned five months, from December 2022 to April 2023, and involved the collection of fish samples from four different floodplain types: river, lebung, lebak kumpei, and rawang. A total of 284 striped snakehead fish were examined, and measurements of length- weight and their reproductive biology were observed. The findings revealed that the sex ratio of striped snakehead fish was skewed toward females, with a ratio of 1:1.7 (females to males). The size at which female striped snakehead fish reach maturity was determined to be 28.5 cm, while male striped snakehead fish matured at 29.30 cm. The peak spawning season for striped snakehead fish occurred in December, coinciding with the rainy season. The spawning grounds for striped snakehead fish were predominantly located in the lebung station in the upper reaches of the Lubuk Lampam Floodplain. Striped Snakehead fish exhibited a partial spawning behavior. Furthermore, these fish demonstrated a relatively high reproductive potential, with fecundity ranging from 5,859 to 30,321 eggs.